2005
DOI: 10.1364/ol.30.001629
|View full text |Cite
|
Sign up to set email alerts
|

Splice-free interfacing of photonic crystal fibers

Abstract: We report a new method for making low-loss interfaces between conventional single-mode fibers and photonic crystal fibers (PCFs). Adapted from the fabrication of PCF preforms from stacked tubes and rods, this method avoids the need for splicing and is versatile enough to interface to virtually any type of index-guiding silica PCF. We illustrate the method by forming interfaces to two problematic types of PCF, highly nonlinear and multicore. In particular, we believe this to be the first method capable of indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…We believe that the stack-and-draw [15] or the die-cast method that is able to realize elliptical-hole and asymmetric PCF structures [16], can be used to fabricate such a structure. While the highly asymmetric mode shape of our proposed PCF design surely makes it more challenging to couple it with conventional optical fibers, such kind of highly birefringent PCFs have been widely proposed and implemented in the real applications and various schemes have been proposed to alleviate the problem [17]. …”
Section: Discussionmentioning
confidence: 99%
“…We believe that the stack-and-draw [15] or the die-cast method that is able to realize elliptical-hole and asymmetric PCF structures [16], can be used to fabricate such a structure. While the highly asymmetric mode shape of our proposed PCF design surely makes it more challenging to couple it with conventional optical fibers, such kind of highly birefringent PCFs have been widely proposed and implemented in the real applications and various schemes have been proposed to alleviate the problem [17]. …”
Section: Discussionmentioning
confidence: 99%
“…The use of the same technique, but repeating arc discharges in SMF, was also studied by Xiao et al [93]. Leon-Saval et al [94] demonstrated a spliceless ferrule interface between an SMF and a PCF adapted from the fabrication of PCF preforms from stacked tubes and rods. Splices between hollow-core fibers and SMF were also studied through the use of electric arc discharges in the region of the SMF (Thapa et al [95], Xiao et al [96]).…”
Section: Splices In Pcf/smfmentioning
confidence: 98%
“…This method, called the "ferrule technique" [24], was the precursor of the photonic lanterns and was used to interface different photonic crystal fibers to single-mode standard stepindex fibers. Nowadays, an all solid optical fiber splitter/ combiner fabrication technique [12] is most commonly used.…”
Section: Different Approachesmentioning
confidence: 99%